Peningkatan Hasil Belajar Tematik Terpadu Peserta Didik Menggunakan Metode Problem Solving Di Sekolah Dasar - Randy Ariesta Almy; Muhammadi Muhammadi (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research is caused by the lack of trained students in solving problems related to problem solving through group collaboration. This research aims to describe the improvement of student learning outcomes on integrated thematic learning using the Problem Solving method. The type of this research is Classroom Action Research using a qualitative and quantitative approach. The study was consistsof two cycles. The research design includes planning, implementation, observation and reflection. The research subjects were students of class IVB of 30 Cengkeh SDN in Padang City. The results of the study showed: a). RPP I cycle 81% cycle II 94% b). Implementation on aspects of the teacher the first cycle 83%, second cycle  94% c). Implementation on aspects of learners first cycle 77% and secondcycle 94% d) Learning outcomes students in first cycle obtaines an average score of 76, cycle II 86. So that,the Problem Solving method can improve student learning outcomes in integrated thematic learning in class IVB SDN 30 Cengkeh, Padang City. Keywords: Problem solving method, improvement of learning outcomes, integrated thematic